(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
The emerging advances in the development of novel drug delivery technologies are likely to have a significant impact on the drug industry. Among the various carriers used for targeting of drugs to various body tissues, the cellular carriers meet several criteria desirable in clinical applications, among the most important being biocompatibility of carrier and its degradation products. Leukocytes, platelets, erythrocyte, and nanoerythrocytes have been proposed as cellular carrier systems. Among these, the erythrocytes have been the most investigated and have found to possess great potential in novel drug delivery. Most of the nano erythrocytes used as drug carriers are rapidly taken up from blood by macrophages of the reticuloendothelial system (RES), which is present in liver, lung, and spleen of the body. Once in the RES, the erythrocyte is attacked by lysosomal enzymes that cause the breakage of the cellular membrane and the degradation of the hemoglobin by the heme-oxygenase enzyme. The use of red cells as carriers of drugs constitutes a field of work that has been barely explored, especially when compared to other carrier systems. From a therapeutic perspective, erythrocytes may be employed for two main purposes. To act as a reservoir for the drug, providing the sustained release of the same into the body, this enables the posology of the drugs to be modified by altering the dose and increasing the dosage intervals. To selectively direct the drugs to the RES (monocyte-macrophage system) of the liver, spleen, and bone marrow, which constitute the usual sites form the destruction of nanoerythrocytes. Nanoerythrosomes (NERs) are prepared by different erythrocyte ghosts to produce small vesicles with an average diameter of 100 nm. Since the NERs are particles, phagocytosis may be involved in their mechanisms of potentiating drugs such as antineoplastic and angiotensin converting enzyme inhibitors and systemic corticosteroids and prodrug. Such cells could be used as circulating carriers to disseminate a drug within a prolonged period in circulation or in target-specific organs, including the liver, spleen, and lymph nodes. A majority of the drug delivery studies using drug-loaded erythrocytes are in the preclinical phase.